Bargaining Power and the Effects of Joint Negotiation: The "Recapture Effect" - Craig T. Peters (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2014)
This paper considers the effects of joint negotiation when suppliers and intermediaries engage in bilateral negotiation over inclusion of a supplier's product in an intermediary's network. I identify conditions under which joint negotiation by two suppliers increases the suppliers' bargaining power even when the suppliers' products are not substitutes for each other. In particular, joint negotiation increases the suppliers' bargaining power if suppliers face smaller losses from disagreement when they negotiate jointly. If joint negotiation causes an intermediary to lose more of its consumers to competing intermediaries in the event of disagreement, and if the suppliers sell their products through these competing intermediaries, the suppliers will be able to recapture more of the sales that they would otherwise have lost in the event of disagreement. As a result, joint negotiation reduces the suppliers' losses from disagreement, and thus enhances their bargaining power. I show that these conditions arise under a wide range of assumptions about consumer preferences.
Keywords: 330